Influential models in the cooperatives of savings and credits in Colombia - Luz Patricia Pardo Martínez (AECOOP Escuela de Estudios Cooperativos, 2017)
This study on the "influential models of cooperatives in Colombia", aims to identify the practices that have the Insured the viability and permanence of such organizations, because have facilitated the development of their Social and Economic as well that of the communities where they operate Members. Identify models or International references have been concerning paragraph these organizations and their degree of influence. The methodology used was the comparative case study method, which provided the opportunity for analysis and reflection of the organizations under study; addressing comparing the influential models between established at national and international level, which at one time were related to cooperative organizations in Colombia, in their practices of savings and credit, raises the reader processes, developments and practices they were decisive for the stability of cooperative savings and credit organizations in each of the historical moments, demarcating their scope marking reach.